Agronomic efficiency and sanitary quality of biofertilizers applied to the soil in organic lettuce cultivation - Moura, Álisson Queiroz; Correa, Elida Barbosa; Fernandes, Josely Dantas; Monteiro Filho, Antonio Fernandes; Ferreira, Tricya Neroyldes Farias; Leão, Alexandre Costa (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
The fertilization of vegetables by means of biofertilizers is mainly used by organic agriculture. However, there are few studies published evaluating the potentially pathogenic microbiota to humans in biofertilizers as well as its formulation according to the nutritional needs of the crop. Thus, the objective of this study was to formulate two optimized biofertilizers and evaluate their sanitary characteristics (microbiological and parasitological) and agronomic efficiency in the organic cultivation of curly lettuce. The experiment was conducted under field conditions in Lagoa Seca, Paraíba. The experimental arrangement was in randomized blocks, in a factorial scheme (2 x 6), with 3 replications, being two optimized biofertilizers (BIO I and BIO II) and six concentrations (0, 20, 40, 60, 80 and 100 mL). The curly lettuce was fertilized with two biofertilizers, formulated with organic materials, and submitted to aerobic fermentation for 96 days. BIO II did not have contamination with microorganisms pathogenic to humans, while BIO I presented contamination with total and fecal coliforms, Ascaris lumbricoides, Ancilostomideo spp., Entamoeba histolystica and Entamoeba coli. The application of BIO I and BIO II promoted an increase in total production yield, commercial production, number of leaves, dry mass of the stem and root. However, the dry mass of leaves did not differ from the control treatment, regardless of biofertilizer. Further studies should be conducted to investigate the residual effect of biofertilizers and other application methods such as foliar spraying for BIO II.